2013
DOI: 10.1017/s0025315413001392
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of infection by the epicaridean parasite,Gyge ovalisand the emergence of intersex in the estuarine mud shrimp,Upogebia major

Abstract: A population of the mud shrimp, Upogebia major, inhabiting Kasaoka Inlet had a higher frequency of intersex males compared to other populations in the Seto Inland Sea, Japan. This population also featured a high prevalence of the branchial epicaridean parasite, Gyge ovalis, and inhabited a tidal flat characterized by increasingly softer sediments going into the lower tidal areas. We examined the rates at which infection co-occurred with intersex features and checked whether infection patterns varied with inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…No migration has been reported for U. major [6], and given the clear sexual dimorphism, sex reversal is not considered to occur [4]. Parasitic infection has been suggested as only a potential cause for intersex [51], and in our study, only fewer than five individuals were identified as intersex among approximately 15,000 shrimp. Additionally, in the studies from Tokyo Bay and Vostok Bay, as well as ours, there were no differences in the lifespan or growth rate of U. major between sexes, except in Namhae [4,54,55].…”
Section: Sex Ratiomentioning
confidence: 47%
See 1 more Smart Citation
“…No migration has been reported for U. major [6], and given the clear sexual dimorphism, sex reversal is not considered to occur [4]. Parasitic infection has been suggested as only a potential cause for intersex [51], and in our study, only fewer than five individuals were identified as intersex among approximately 15,000 shrimp. Additionally, in the studies from Tokyo Bay and Vostok Bay, as well as ours, there were no differences in the lifespan or growth rate of U. major between sexes, except in Namhae [4,54,55].…”
Section: Sex Ratiomentioning
confidence: 47%
“…Studies have been conducted on the larval development of U. major [46,47], its burrow structure [2,48], parasitism and commensalism [49][50][51][52], sexual dimorphism [53], life history, and the ecological characteristics [6,8]. Population characteristics have been studied in Tokyo Bay, Japan, and Vostok Bay, Russia [4,54].…”
Section: Introductionmentioning
confidence: 99%
“…The host of the types was originally reported as Upogebia major (De Haan, 1841) in Shiino (1939b) but was changed to U. issaeffi (Balss, 1913) in Shiino (1958) and back again to U. major in Shiino (1972). This species has been reported several times from U. major, including in a large-scale study of the host/parasite relationship by Ubaldo et al (2014), but only once subsequently from U. issaeffi (Itani 2004b). The identity of the type host is therefore most likely U. major, but only examination of the type host can solve this question.…”
Section: Key To Females Of Species Ofmentioning
confidence: 99%
“…Therefore, although Axiidea+Gebiidea is a paraphyletic grouping, it is useful to consider their constituent species as a morphologically homogenous host assemblage from the perspective of their bopyrid parasites. Ecologically, bopyrids are known to infest mud shrimps at some of the highest reported prevalence levels for these parasitic isopods, having the potential to dramatically impact host populations, and thus their hosts' potential for bio-engineering of soft bottom ecosystems (Griffen 2009;Ubaldo et al 2014;Pascal et al 2016;Dairain et al 2017). Mud shrimps are also host to the only documented case of an introduced epicaridean parasite Chapman et al 2012;Hong et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some species might be parasitic to thalassinideans; e.g., isopods are prevalent ectoparasites of Upogebia (Leach, 1814) (for example, see [4,5,[81][82][83]). There are also endoparasites of thalassinids, such as trematode cysts, Acanthocephala [4], and copepods infesting gills, pereiopods, and egg masses (e.g., [68]).…”
Section: Ecological Relationshipsmentioning
confidence: 99%